A comparative study on endothelial cell loss in nanophthalmic eyes undergoing cataract surgery by phacoemulsification - Rajendrababu, Sharmila (Indian J Ophthalmol, 2021)
PURPOSE: The purpose of this study is to compare the endothelial cell loss (ECL) in nanophthalmic eyes and age-matched controls undergoing cataract surgery by phacoemulsification and also to identify the risk factors influencing the endothelial cell density (ECD). This was a prospective comparative interventional case series. METHODS: We enrolled 19 nanophthalmic eyes (study group) and 42 age-matched cataract controls (control group) undergoing phacoemulsification after meeting the inclusion criteria. Ocular parameters like best-corrected visual acuity, intraocular pressure, pachymetry, specular microscopy, and slit lamp findings were noted preoperatively and at month 1 and 3 postsurgery. All nanophthalmic eyes underwent cataract surgery with concomitant prophylactic posterior sclerostomy. RESULTS: The median percentage endothelial loss in nanophthalmic eyes was 4.0 (IQR 0–23.5), 7.4 (IQR 1.0–-22.4) at 1 and 3 months postoperatively compared to 6.3 (IQR 1.7–14.1) and 6.4 (IQR 2.6–-12.1) in age controlled normal eyes (P = 0.94, P = 0.46, respectively). Linear regression analysis showed increasing age as the only variable influencing the percentage decrease in corneal ECD in the study group (P = 0.001). Nanophthalmic eyes with ACD <2.5 mm had a significantly greater reduction in ECD at 3 months postcataract surgery compared to baseline (P = 0.039). Visual outcomes and IOP reduction in the study group with ACD >2.5 mm were significantly better postcataract surgery (P = 0.02 and P = 0.002, respectively). CONCLUSION: The percentage of ECL in nanophthalmic eyes undergoing phacoemulsification is equivalent to normal eyes. However, in the nanophthamic eyes with AC depth <2.5 mm, the percentage cell loss was significantly higher warranting the need for extensive intraoperative care. Increasing age was found to be the only significant risk factor influencing the ECD in short eyes.